Hyponatremic-hypertensive Syndrome in a 19-month-old Boy with Renovascular Hypertension - Mehtap Akbalik Kara; Beltinge Demircioglu Kilic; Suleyman Cuneyt Karakus; Nimet Sahin; Mithat Buyukcelik; Ayse Balat (Saudi Journal of Kidney Diseases and Transplantation, 2022)
Hyponatremic-hypertensive syndrome (HHS) is an uncommon disorder rarely seen in children. Herein, we report a 19-month-old boy with HHS. He had severe hypertension, polyuria, polydipsia, vomiting, and seizure at presentation. Laboratory findings revealed hyponatremia, hypokalemia, metabolic alkalosis, proteinuria, hypercalciuria, high levels of renin and aldosterone, and renal artery stenosis. All symptoms resolved after nephrectomy. Clinicians should be aware of this syndrome because prompt recognition can be lifesaving.